Sistem Penilaian Manajemen Stres dengan Variabel Fuzzy pada Pasien Rumah Sakit - Dhina Puspasari Wijaya; Dadang Heksaputra; Muhamad Irfanudin (Universitas PGRI Kanjuruhan Malang, 2020)
Hospitals are often associated with experiences about illness, hospitals help solve problems about the disease, but hospitals also provide services about childbirth. The inpatient process is a very traumatic experience for male or female. In the stress management system, several factors have been affected, but stress has not yet been utilized. Questionnaire from the question of the total has several weights at each point. The weighting of each questionnaire points has one weight so that the results of each item will be added. Each question represents each output point. In Figure 2, the results of the DAS-42 assessment will be categorized into three membership functions, namely Depression, Anxiety, and Stress. Calculation of stress management status assessment grouping is tested using assessment calculation. Each question point in the form uses the point grouping reference dass42. The cluster of question points according to the fuzzy variable set members is shown in Figure 2, Figure 3, Figure 4, and Figure 5. The test was declared valid by psychiatrists and psychiatrists.